Financial Development and Pre-historic Geographical Isolation: Global Evidence - Oasis Kodila-Tedika; Simplice Asongu; Matthias M. Cinyabuguma; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2017)
Using cross-country differences in the degree of isolation before the advent of technologies in sea and air transportation, we assess the relationship between geographic isolation and financial development across the globe. We find that pre-historic geographical isolation has been beneficial to development because it has contributed to contemporary cross-country differences in financial intermediary development. The relationship is robust to alternative samples, different estimation techniques, outliers and varying conditioning information sets. The established positive relationship between geographic isolation and financial intermediary development does not significantly extend to stock market development.
Keywords: F15; G15; N7; O16; O50; 330; Financial development; Isolation; Agglomeration; Globalization